EMPOWERING VILLAGE COMMUNITIES THROUGH DIGITAL LITERACY BASED ON THE UTILIZATION OF E-COMMERCE IN KARANGSARI VILLAGE - KULON PROGO - Sitorus, Siti Hazar; Suriani, Julis; Maharani, Reizki; Azwar, Azwar; Rafdeadi, Rafdeadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research aims to explore how digital literacy can empower the village community of Karangsari, Kulon Progo, through the use of e-commerce. With increasing access to the internet and digital technology, Karangsari Village holds significant potential to enhance its local economy via e-commerce platforms. The study employs a qualitative approach, involving in-depth interviews, observations, and documentation with micro, small, and medium-sized enterprises (MSMEs), as well as direct observation of community empowerment activities conducted by the Yogyakarta Communications and Informatics Office. Findings reveal that while substantial support for internet infrastructure in the village is crucial, it must be accompanied by high-quality digital literacy education to be truly effective. Strengthening digital literacy can improve the community’s ability to raise their standard of living—particularly by enabling MSME actors to market their products online, thereby increasing income and overall community welfare. The study concludes that more structured and sustainable digital literacy training programs are essential to effectively support the empowerment of rural communities in the digital era.